2018
DOI: 10.21037/atm.2017.10.18
|View full text |Cite
|
Sign up to set email alerts
|

Asian-Indians: a review of coronary artery disease in this understudied cohort in the United States

Abstract: Coronary artery disease (CAD) is a major cause of cardiovascular death worldwide. Prevalence of CAD is highly variable among different races. Asian Indians have been noted to have the highest CAD rates and the conventional risk factors fail to explain this difference completely. Asian Indians constitute a fifth of the global population, and the higher rates of CAD in this population constitute a major health challenge.There have been studies in the early 2000s that investigate the risk factors in this populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 55 publications
1
21
0
Order By: Relevance
“…Both high cholesterol and hypertension are risk factors for diabetes and heart disease. While the high prevalence of diabetes and heart disease among Asian Indians is well established [74][75][76], a significantly lower risk for coronary heart disease was found for Chinese compared to NHWs [77]. Moreover, a study examining functional limitations among middle-aged and older adults reported that Asian Indians had higher odds for functional limitations compared to Chinese [78].…”
Section: Discussionmentioning
confidence: 99%
“…Both high cholesterol and hypertension are risk factors for diabetes and heart disease. While the high prevalence of diabetes and heart disease among Asian Indians is well established [74][75][76], a significantly lower risk for coronary heart disease was found for Chinese compared to NHWs [77]. Moreover, a study examining functional limitations among middle-aged and older adults reported that Asian Indians had higher odds for functional limitations compared to Chinese [78].…”
Section: Discussionmentioning
confidence: 99%
“…Coronary artery disease (CAD) is a major CVD phenotype being noticed in Indians. It is estimated that Asian Indians constitute a fifth of the global population with CAD [2]. CAD is a complex disease resulting from the cumulative and interactive effects of large number of genes along with environmental exposure.…”
Section: Introductionmentioning
confidence: 99%
“…81 If the CVD risk in the Indian population did not decline upon immigration to foreign countries, a genetic factor was a possibility while the lifestyle also fueled the excessive risk of CVD. 82…”
Section: Genetics and Lifestylesmentioning
confidence: 99%